The Dynamics of Disagreement - Daniel, Kent; Klos, Alexander; Rottke, Simon (Review of Financial Studies, 2023)
Abstract In this paper, we infer how the estimates of firm value by “optimists” and “pessimists” evolve in response to information shocks. Specifically, we examine returns and disagreement measures for portfolios of short-sale-constrained stocks that have experienced large gains or large losses. Our analysis suggests the presence of two groups, one of which overreacts to new information and remains biased over about 5 years, and a second group, which underreacts and whose expectations are unbiased after about 1 year. Our results have implications for the belief dynamics that underlie the momentum and long-term reversal effect. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.